Epigallocatechin-3-gallate and epicatechin-3-gallate from green tea decrease plasma non-transferrin bound iron and erythrocyte oxidative stress - C. Thephinlap (2018)
β-Thalassemia patients suffer from secondary iron overload caused by increased iron absorption and multiple blood transfusions. Excessive iron catalyzes free-radical formation, causing oxidative tissue damage. Non-transferrin bound iron (NTBI) detected in thalassemic plasma is highly toxic and chelatable. Desferrioxamine and deferiprone are used to treat the iron overload, but many side effects are found. Epigallocatechin gallate (EGCG) and epicatechin gallate (ECG) in green tea (GT) show strong antioxidant properties. We separated the EGCG and ECG from GT extract using an HPLC, and examined their iron-binding and free-radical scavenging activities. They bound Fe3+ rapidly to form a complex with a predominant absorption at 560 mn. EGCG and ECG bound chemical Fe3+ and chelated the NTBI in a time- and dose dependent manner. They also decreased oxidative stress in iron-treated erythrocytes. In conclusion, EGCG and ECG could be natural iron chelators that efficiently decrease the levels of NTBI and free radicals in iron overload. © 2007 Bentham Science Publishers Ltd.